Sistem Monitoring Status Meja Pada Restoran Berbasis Internet of Things (IOT) - Mardewi, Mardewi; Iskandar, Imran; Sofyan, Sofyan; La Wungo, Supriyadi; Aziz, Firman (Journal of System and Computer Engineering, 2023)
The condition of a busy restaurant sometimes makes it difficult for waiters to monitor and provide satisfactory service to customers. Customers must wave when they want to call waiters but feel ignored or not seen and will feel uncomfortable with the atmosphere and calm in the dining room. An Internet of Things (IOT) based desk status monitoring system is a concept that has the ability to transfer data over a network without the need for human-to-human interaction. This study proposes a table status monitoring system in IOT-based restaurants. This tool is made so that it can be applied to large rooms and crowded visitors. A device equipped with wireless communication to send data to the server, so that it can be monitored in real time. If the button on the tool is pressed, the system will send a signal to the relay to give a call sign warning to restaurant staff/waitresses. The results of this study indicate that status information from tables requesting service from waiters will respond to these service requests and help optimize service at restaurants so that they can satisfy their customers.